1995
DOI: 10.1111/j.1549-0831.1995.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Informal Work in Nonmetropolitan Pennsylvania1

Abstract: It is well recognized that the informal economy—unregulated economic activities that generate real or in‐kind income—features prominently in the day‐to‐day lives of many in the developing world. Researchers have begun to explore the informal economy in developed countries but this work has focussed primarily on urban areas to the neglect of rural areas. In this paper the nature and correlates of informal work in nonmetropolitan Pennsylvania are described through an analysis of survey data on 505 families. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 7 publications
(7 reference statements)
4
57
0
2
Order By: Relevance
“…However, others have not found a relationship between income levels (a proxy for hardship) and self-provisioning activities (Jensen et al 1995). Brown et al (1998) even found that households with higher incomes were more likely to participate in self-provisioning than those experiencing economic hardship.…”
Section: Self-provisioning Economic Hardship and Cultural Identitymentioning
confidence: 96%
“…However, others have not found a relationship between income levels (a proxy for hardship) and self-provisioning activities (Jensen et al 1995). Brown et al (1998) even found that households with higher incomes were more likely to participate in self-provisioning than those experiencing economic hardship.…”
Section: Self-provisioning Economic Hardship and Cultural Identitymentioning
confidence: 96%
“…In late 2005 and early 2006, therefore, 600 faceto-face interviews were conducted. Grounded in the recognition that the extent and character of the off-the-books economy varies markedly across both affluent and deprived populations, as well as urban and rural areas (Jensen et al 1995;Renooy 1990;Williams 2004;Williams and Windebank 1998), a maximum variation sampling method was employed to select four contrasting localities. Firstly, and in the capital of Kiev, an affluent area was chosen, namely Perchersk, along with a deprived neighbourhood, namely Vynogardar.…”
Section: Studying Off-the-books Entrepreneurs In Ukrainementioning
confidence: 99%
“…Women engage in service activities such as commercial cleaning, domestic help, childcare and cooking. Men, on the other hand, are argued to largely conduct what are conventionally seen as 'masculine tasks' such as building and repair work (Fortin et al, 1996 ;Jensen, Cornwell, & Findeis, 1995 ). So, not only is the informal economy characterised by the same sector divisions as the formal economy, but the gender disparities in wage rates prevalent in the formal economy appear to be replicated in the informal economy.…”
Section: Women's Entrepreneurship In the Informal Economymentioning
confidence: 95%